Detection of Nunation Vowelization Types in The Quran Diacritical Marks Using Automated Text- Processing Algorithms: اكتشاف تنوين التركيب وتنوين التتابع في الضبط القرآني باستخدام خوارزميات المعالجة النصية الآلية - Amir Adel Mabrouk Eldeib, Moulay Ibrahim El- Khalil Ghembaza (مجلة العلوم الهندسية و تكنولوجيا المعلومات, 2020)
The science of diacritical marks is closely related to the Holy Quran, as it was used in the Quran to remove confusion and error from the pronunciation of the reader, so the introduction of any technique in the process of processing Quranic texts will have an effect on facilitating the tasks of researchers in the field of Quranic studies, whether on the reader of the Quran, to help him read accurate and correct recitation, or on the tutor to help him compile a number of examples appropriate for training. The importance of this research lies in employing automated text- processing algorithms to determine the locations of the Nunation vowelization types in the Holy Quran, and the possibility of their computerizing in order to facilitate the accurate recitation of the Holy Quran and, at the same time, to collect training examples in a database or building a corpus for future use in many research and software applications for the Holy Quran and its sciences. This research aims to present a new idea through the proposition of a framework architecture that identifies and discover automatically the locations and types of the Nunation in the Holy Quran based on the part- of- speech tagging algorithm for Arabic language so as to determine the type of words, and then by using a knowledge base to discover the appropriate Nunation words and their locations, and finally discovering the type of Nunation so as to determine the vowelization of the last letter of each Nunation word according to the Quran diacritical marks science. Furthermore, another benefit is to link searching processes with Quranic texts towards extracting the composition Nunation and the sequence Nunations in the Holy Quran emerges from the science of Quran diacritical marks; and display them as data according to a set of options selected by the user through suitable applications interfaces. The basic elements that the results of searching Quranic texts should display are highlighted, in order to extract the positions and types of Nunation vowelizations. As well as, a template for the results of searching all types of Nunation in a specific Quranic Chapter is given, with several possible options to retrieve all data in detail.